Spanish ecological battleground: population structure of two invasive fungi, Cryphonectria parasitica and Fusarium circinatum - Ahmad, Farooq; Diez, Julio Javier (Frontiers in Plant Science, 2023)
Invasive fungi distributed worldwide through globalization have caused devastating diseases in different forests, causing economic and ecologic disturbances. Two such invasive species are Cryphonectria parasitica and Fusarium circinatum, which were introduced to Europe from North America, separated temporally: C. parasitica was introduced about nine decades ago, whereas F. circinatum was introduced around two decades ago. As C. parasitica had a longer time to undergo genetic changes, we hypothesized that it has higher genetic diversity than the recently introduced F. circinatum in Spain. In addition, we studied the genetic characterization of both fungi present in similar ecological conditions in Northern Spain with the aim of providing data for biocontrol measures. Molecular genetic markers were used to test these hypotheses, including mating type and DNA sequencing of internal transcribed spacer (ITS) regions. In addition, we used vegetative compatibility (VC) type markers in C. parasitica as the information about VC type is essential to apply biocontrol against the fungus. All the isolates of C. parasitica from the studied area belonged to only one VC type (EU-1) and one mating type (MAT-2). However, three distinct haplotypes of C. parasitica were identified through ITS sequencing, showing that multiple introductions might have happened to Cantabria. Among F. circinatum, no diversity was observed in ITS and MAT loci in the studied area but isolates from other Spanish regions showed the presence of both mating types. Overall, C. parasitica had higher genetic diversity than F. circinatum, despite both organisms appearing to reproduce clonally. This study helped understand the invasion patterns of C. parasitica and F. circinatum in northern Spain and will be useful in applying biocontrol measures against both pathogens.